Pandemi Covid -19: Dampaknya Terhadap Kinerja Keuangan Sektor Makanan dan Minuman - Yuda, Fairas Panca; Mubarakah, Septyana (Politeknik Raflesia Press, 2024)
Financial performance in many literacies is affected by aspects such as Net Profit Margin, Current Ratio, and Debt To Equity Ratio. This research wants to further test the effect on company performance due to the COVID-19 pandemic with a sample of the food and beverage subsector which is included in the sample criteria. A purposive sampling technique was carried out to obtain 105 analysis samples with Eviews 12, using multiple linear regression analysis data analysis techniques in the processing. The results of this research reveal that Net Profit Margin (NPM), Current Ratio (CR), and Debt-to-Equity Ratio (DER) influence company performance. Simultaneously, the variables Net Profit Margin (NPM), Current Ratio (CR), and Debt To Equity Ratio (DER) influence company performance